Studi Literatur “Menjawab Tantangan Keperawatan Gawat Darurat dan Kritis” - mohamad judha (TRIAGE Jurnal Ilmu Keperawatan, 2025)
Introduction: Emergency nursing in hospitals is an important aspect of the health care system that aims to provide immediate care to patients in critical condition. Emergency nurses have a vital role in identifying, assessing, and providing appropriate interventions in life-threatening situations. Methods: A literature search from CINAHL, Scopus, PubMed, International Anesthesia Research Society (IARS), and Google Scholar 2010-2024, on this topic using emergency nursing as a keyword showed 8 related articles. Objective: to explore the challenges and best practices in emergency nursing, including the importance of continuing education and training for nurses. Results: The results of the study showed that improving nurses' skills and knowledge can have a positive impact on patient outcomes. In addition, adequate managerial support and resources also contribute to nurse performance in the emergency unit. Conclusion: With the increasing number of medical emergencies, it is important for hospitals to develop effective strategies in emergency nursing management to improve the quality of care and patient safety